Вычислите, применив распределительный закон:

3/5*(-5/11+5/3)-5/11*(-3/5+11/5)=

11/12*(23/37-12/11)+23/37*(-11/12+37/23)=

4/5*(6/7-5/4)+6/5*(5/6-4/7)=

11/13*(13/22-3/7)+3/13*(-13/3+11/7)=

2

Ответы и объяснения

  • iras8
  • светило науки
2013-02-24T16:53:34+04:00

3/5*(-5/11+5/3)-5/11*(-3/5+11/5)=-3/5*5/11+3/5*5/3+5/11*3/5-5/11*11/5=-3/11+1+3/11-1=0

 

11/12*(23/37-12/11)+23/37*(-11/12+37/23)=11/12*23/37-11/12*12/11-23/37*11/12+37/23*23/37=-1+1=0

 

4/5*(6/7-5/4)+6/5*(5/6-4/7)=4/5*6/7-4/5*5/4+6/5*5/6-6/5*4/7=0

 

Лучший Ответ!
2013-02-24T17:25:38+04:00

3/5*(-5/11+5/3) - 5/11*(-3/5+11/5) = -3/5*5/11 + 3/5*5/3 + 5/11*3/5 - 5/11*11/5 = -3/11 + 1 + 3/11 - 1 = 0

 

11/12*(23/37-12/11) + 23/37*(-11/12+37/23) = 11/12*23/37 - 11/12*12/11 - 23/37*11/12 + 37/23*23/37 = -1 + 1 = 0

 

4/5*(6/7-5/4) + 6/5*(5/6-4/7) = 4/5*6/7 - 4/5*5/4 + 6/5*5/6 - 6/5*4/7 = 0

 

11/13*(13/22-3/7) + 3/13*(-13/3+11/7) = 11/13*(13/22-3/7) + 3/13*(11/7-13/3) = 11/13*13/22 - 11/13*3/7 + 3/13*11/7 - 3/13*13/3 = 11/22 - 33/91 + 33/91 - 1 = 0,5 - 1 = - 0,5